The effect of complete denture wearing on food preference and nutrition of patients in the Prosthodontic Section of the UP Manila College of Dentistry - Delos Reyes, Joanne RJ G.; Mayores, Maxine Erika A.; Ramos, Tristan Nathaniel C.
Introduction: This study aims to determine the effect of complete denture wearing on food preference and nutrition of edentulous patients in the Prosthodontic Section of the UP Manila College of Dentistry.
Methodology. The study involved two groups of patients, complete denture wearers and dentate. Thirty-five patients were selected for each of the two groups. The complete denture-wearing group consisted of completely edentulous patients with existing dentures while the dentate group consisted of patients from the Oral diagnosis section of the College of Dentistry. The participants underwent a guided interview and were asked to accomplish a seven-day food diary. The nutritional adequacies based on the completed food diaries were analyzed using a menu evaluation software and were compared against the Recommended Energy Nutrient Intake (RENI) of 2003. T-test was used for further data analysis.
Results and Discussion. It was observed that both groups have a varied food intake; however, the variety was wider for the dentate group compared to the complete denture wearing group. Dietary energy intake was high for both groups when compared against the Recommended Energy Nutrient Intake (RENI). Based on their food intakes, both the complete denture wearing and dentate groups have adequate nutrition. Complete denture wearing in this study does not significantly affect the food choices for the participants. Also, the nutritional adequacy of the complete denturel-wearing group is higher compared to the dentate group.
Conclusion. Food preference and nutrition is not affected by complete denture wearing of edentulous patients. Food intake is still dependent on an individual's food choice.
Thesis--(Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Complete dentures